A sustainable adsorbent for removal of ammoniacal nitrogen from landfill leachate: Isotherms modelling - Rosli, Mohd Arif; Daud, Zawawi; Ridzuan, Mohd Baharudin; Mat Daud, Azra Munirah; Al Madhoun, Wesam; Yahya, Izat (2023)
There is growing concern to determine an alternative adsorbent for remediating landfill leachate effluent with minimal environmental impact and operational cost. In this work, four low cost sustainable biocomposite materials such as limestone, peat, activated carbon and zeolite were employed as an adsorbent media in an adsorption batch study for the removal of ammoniacal nitrogen from landfill leachate. Isotherm adsorption models of Langmuir and Freundlich were utilized to analyze the adsorption data. The Langmuir isotherm model showed the best fit for experimental data with a maximum monolayer adsorption capacity of 26.18 mg/g which is indicated that the ammoniacal nitrogen adsorption took placed on the surface of biocomposite with monolayer formation of the adsorbate at a specific homogeneous site. The adsorption isotherm follows Langmuir’s model (R2 = 0.99) and Freundlich’s model (R2 = 0.98